



 
CB, I'm going to illustrate with a similar problem. a ln(b) = ln(b^{a}) and ln(a * b) = ln(a) + ln(b) Thus 2 ln(3) = ln(3^{2}) = ln(9) and hence ln(1/3 x^{2}) + 2 ln(3) = ln(1/3 x^{2}) + ln(9) = ln(1/3 * 9 x^{2}) = ln(3 x^{2}) Hence ln(1/3 x^{2}) + 2 ln(3) = ln(15 x) becomes ln(3 x^{2}) = ln(15 x) or 3x^{2} = 15x Therefore 3x^{2}  15x = 0 Hence x = 0 or x = 5. But ln(0) is undefined so the only solution is x = 5. I hope this helps,  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 